Influence of reduced-gravity treadmill running on sensor-derived biomechanics - Santos, B. P.; DeJong Lempke, A. F.; Higgins, M. J.; Hertel, J. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Reduced gravity treadmills have become increasingly prevalent in clinical settings. The purpose of this study was to assess the influence of manipulated levels of bodyweight during reduced gravity treadmill running on sensor-derived spatiotemporal, kinematic, and kinetic measures.